Lithium ion battery and electric device
By establishing mathematical models and adjusting the positive electrode active materials and electrolyte formula in lithium-ion batteries, the problem of uneven diffusion of lithium-ion batteries during high-speed discharge is solved, and the battery is efficient discharge and long-term cycle life is achieved.
Patent Information
- Application Number
- CN202510091523.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
When lithium-ion batteries are discharged at high magnification, the diffusion of lithium ions in the positive electrode active material layer is uneven, resulting in low charging and discharging efficiency and inability to improve the power density. The diffusion coefficients of the electrolyte and the positive electrode active material do not match, affecting the stability and cycle life of the battery.
By establishing a mathematical model, defining A=(log(M)+R)^2 and B=log(E/M)+R, using the ratio of A/B to quantify the discharge performance of the battery, combining experimental measurement data, adjusting the formula of the positive electrode active material and electrolyte to ensure that the diffusion speed of lithium ions in the electrolyte and the positive electrode active material layer matches, supports high-magnification output and maintains long-term cycle life.
The continuous and stable output of lithium-ion batteries during high-rate discharge is achieved, the discharge efficiency and power density of the battery are improved, and the cycle life of the battery is extended, avoiding overheating and shortening of the battery life due to excessive discharge current.
Smart Images

Figure CN119920831A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrical devices, and in particular to a lithium-ion battery and an electrical device. Background Art
[0002] With the rapid development of lithium-ion battery technology, the performance optimization of lithium-ion batteries has become an important research topic. Among them, the diffusion coefficient of the positive electrode material is one of the important factors that determine the battery's charge and discharge efficiency. During high-rate discharge, whether lithium ions can diffuse quickly and evenly in the positive electrode active material layer is the key to improving the battery's discharge efficiency and power density.
[0003] However, the electrolyte is the medium for ion transmission in the battery, and the diffusion coefficient E of lithium ions in the electrolyte and the diffusion coefficient M of the positive electrode active material must match. Specifically, when the diffusion coefficient E of the electrolyte is significantly greater than the diffusion coefficient M of the positive electrode active material, the lithium ions accumulated on the surface of the positive electrode active material layer cannot diffuse to the inner layer of the positive electrode active material layer in time, and the locally accumulated lithium ions produce stress on the positive electrode active material layer, which is easy to cause hidden dangers such as cracking on the surface of the positive electrode active material layer; when the diffusion coefficient E of the electrolyte is significantly less than the diffusion coefficient M of the positive electrode active material, the lithium ion content around the positive electrode active material is insufficient, it is difficult to maintain the high rate discharge demand, and the power density cannot be improved. Therefore, the matching of the diffusion coefficient E of the electrolyte and the diffusion coefficient M of the positive electrode active material is an element to ensure the continuous and stable high rate output and long cycle life of lithium-ion batteries. Exploring the correlation between the output rate, the diffusion coefficient E of the electrolyte and the diffusion coefficient M of the positive electrode active material and establishing a corresponding model have become urgent problems to be solved. Summary of the invention
[0004] In order to solve the above problems and realize the continuous stable high rate output and long cycle life of lithium ion batteries, the first aspect of the present application provides a lithium ion battery, including a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte for transmitting lithium ions, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector and containing a positive electrode active material, wherein the lithium ion diffusion coefficient of the positive electrode active material at room temperature is M cm 2 / s, the lithium ion diffusion coefficient of the electrolyte at room temperature is E cm 2 / s, the maximum discharge rate supported by the lithium-ion battery is RC, which satisfies:
[0005] A=(log(M)+R) 2 ;
[0006] B = log (E / M) + R;
[0007] 0≤A / B≤0.5.
[0008] By establishing a mathematical relationship model between the lithium ion diffusion coefficient M of the positive electrode active material, the lithium ion diffusion coefficient E of the electrolyte and the maximum discharge rate RC supported by the lithium ion battery, based on this mathematical model and combined with the corresponding experimental measurement data, on the one hand, after determining the value or range of any one of M, E, and R, the range of the other two data is solved, and the battery system is improved and adjusted in a targeted manner to obtain a lithium ion battery in which M and E are adapted, the diffusion rate of lithium ions in the electrolyte and the positive electrode active material layer is sufficient to support continuous and stable output at the RC rate and maintain a long cycle life; on the other hand, for finished batteries that have been assembled, the mathematical model can also be used to evaluate battery performance, solve the maximum output rate RC actually supported by the lithium ion battery, avoid battery overheating and shortened life due to excessive discharge current, and provide guidance for the long-term use of the battery.
[0009] In some optional embodiments, the positive electrode active material layer comprises the following components:
[0010] The positive electrode active material, as the positive electrode active material, has a weight percentage of 80% to 97%;
[0011] Conductive agent, 2% to 10% by weight; and
[0012] The binder has a weight percentage of 1% to 10%.
[0013] In some optional embodiments, the crystalline phase of the positive electrode active material is one of a layered structure crystalline phase, a spinel structure crystalline phase, and an olivine structure crystalline phase. The layered structure allows lithium ions to be intercalated and deintercalated between layers, providing a higher specific capacity and good electrochemical performance, and thus has a high theoretical capacity to enhance the energy storage performance per unit volume of the battery. The spinel or olivine crystalline phase provides a stable structural framework, effectively enhancing the overall stability of the positive electrode active material layer, and providing the necessary conditions for the high rate output of the battery.
[0014] In some optional embodiments, the positive electrode active material of the layered structure crystal phase is lithium nickel cobalt metal oxide, chemical formula LiNi x Co y D z O2, where 0.6≤x≤0.9, 0.1≤y≤0.4, z=1-x–y, and D is Mn or Al;
[0015] The positive electrode active material of the spinel structure crystal phase is lithium manganese oxide LiMn2O4;
[0016] The positive electrode active material of the olivine structure crystal phase is lithium iron phosphate LiFePO4 or lithium iron manganese phosphate LiMn x Fe 1-x PO4, 0.1≤x≤0.8.
[0017] In some optional embodiments, the positive electrode active material further comprises a doping element, and the doping element is at least one of Al, Zr, Sr, Sb, Mg, Ti, W, Nb, Y, Ca, Ba, B, and F. Any of the doping elements improves the cycle performance and stability of the positive electrode active material layer by lattice doping and substitution, surface modification and coating, improving electronic and ionic conductivity, reducing cation mixing and / or inhibiting lattice oxygen loss.
[0018] In some optional embodiments, the surface of the positive electrode active material is further modified by coating and / or atomic doping, wherein the coating modification includes coating a layer of metal oxide nanolayer on the surface of the positive electrode active material, and the atomic doping modification includes doping the surface of the positive electrode active material with metal atoms having an electronegativity less than 2. The protective film is formed by the coating, and the direct contact between the positive electrode active material and the electrolyte is reduced, thereby inhibiting the occurrence of side reactions, reducing the deactivation of the positive electrode active material, and improving the cycle performance of the battery; the atomic doping modification can change the electronic structure and lattice parameters of the positive electrode active material, and improve the structural stability and electrochemical performance of the material.
[0019] In some optional embodiments, the electrolyte comprises the following components:
[0020] A lithium salt, including lithium hexafluorophosphate, wherein the total molar concentration of the lithium salt is 0.5M-2.0M;
[0021] The organic solvent mixture comprises one or more of ethylene carbonate, dimethyl carbonate, fluoroethylene carbonate and vinyl sulfate.
[0022] In some optional embodiments, a modification additive is further added to the electrolyte, and the modification additive includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate) and triethyl phosphate, and the weight ratio of the additive to the electrolyte system is 0.5%-2%. Lithium bis(fluorosulfonyl)imide can improve the conductivity of the electrolyte, thereby improving the lithium ion diffusion coefficient E of the electrolyte; lithium bis(oxalatoborate) does not contain fluorine, which reduces the generation of byproduct fluoride and reduces the risk of thermal runaway of the battery under high temperature conditions; triethyl phosphate can be used as a flame retardant to improve the thermal stability of the electrolyte system and ensure the safety of the battery.
[0023] In some optional embodiments, the positive electrode sheet satisfies at least one of the following conditions:
[0024] (a) The single-sided surface density of the positive electrode sheet is 8-14 mg / cm 2 ;
[0025] (b) The tap density of the positive electrode sheet is 2.6 - 4.2 g / cm 3 ;
[0026] (c) The specific surface area of the positive active material particles is 0.1 - 25 m 2 / g;
[0027] (d) The particle size D10 - D90 distribution of the positive active material particles is 1 - 25 μm.
[0028] In some alternative embodiments, the test method for the lithium ion diffusion coefficient M of the positive active material includes:
[0029] S11: Take the positive electrode sheet, lithium sheet, and the separator included in the lithium ion battery to make a button-type half cell, calibrate the capacity at a rate of 0.1C at room temperature, and then charge it to 50% of its calibrated capacity at a rate of 0.1C and leave it standing for 15 min;
[0030] S12: Then, charge the button-type cell at a constant current of 0.1C at room temperature for 5 min, record the initial charging voltage V1 and the final charging voltage V2, then stop charging and leave it standing for 15 min, and record the initial standing voltage V3 and the final voltage V4;
[0031] S13: The calculation formula for the lithium ion diffusion coefficient M of the positive active material is: M = (4 / πτ) * [(mV / nS)]^2 * [(ΔEs / ΔEt)]^2, where τ is the time for applying the constant current and τ << L^2 / M, m is the mass of the positive active material included in the positive electrode sheet, V is the molar volume of the positive active material in cm^3 / mol, n is the relative molecular mass of the positive active material in g / mol, S is the contact area between the positive electrode sheet and the electrolyte in cm 2 , ΔEs = V4 - V1, ΔEt = V3 - V2, and L is the thickness of the positive active material layer included in the positive electrode sheet.
[0032] In some alternative embodiments, the test method for the lithium ion diffusion coefficient E of the electrolyte includes:
[0033] S21: Take the electrolyte and the separator included in the lithium ion battery, measure the tortuosity ε of the separator, and use the electrolyte, the separator, and two lithium sheets to make a button-type cell, where the two lithium sheets serve as the two electrodes of the button-type cell;
[0034] S22: Apply a constant alternating positive and negative current pulse of 0.2 mA / cm 2 to the button-type cell at room temperature for 30 minutes, and then turn off the current;
[0035] S23: measuring the change of the open circuit voltage (OCV) of the button battery over time to obtain an OCV relaxation curve; and
[0036] S24: The calculation formula of the lithium ion diffusion coefficient E of the electrolyte is E=d^2*k*ε / (π^2), d is the thickness of the diaphragm, k is the natural logarithmic slope of the OCV relaxation curve, and ε is the tortuosity of the diaphragm.
[0037] In some optional implementations, the test method of the maximum discharge rate RC includes:
[0038] S30: The test environment is room temperature: 25±2° C., and the lithium-ion battery during the test is not subjected to forced heating or cooling by air flow or liquid flow;
[0039] S31: at room temperature, charging the lithium-ion battery to a cut-off voltage at a rate of 0.1C, and standing for 30 minutes;
[0040] S32: at room temperature, discharge the lithium ion battery to the cut-off voltage at a rate of 0.1C, leave it to stand for 30 minutes, and record the discharge specific capacity; and
[0041] S33: Repeat S31 and S32, taking 0.5C rate as the basis, increasing the discharge rate by 0.5C each time until the discharge specific capacity at the discharge rate of RC is less than or equal to 80% of the discharge specific capacity at the discharge rate of 0.1C for the first time, RC being the maximum discharge rate supported by the lithium-ion battery.
[0042] The second aspect of the present application provides an electric device, comprising a lithium-ion battery according to any one of the above items. Since the lithium-ion battery has the above-mentioned beneficial effects, the electric device provided by the present application has the characteristics of continuous stable high-rate output and high cycle retention rate.
[0043] This application also has at least the following technical effects:
[0044] 1) By precisely controlling the various physical properties and diffusion coefficient M of the positive electrode active material, it is ensured that lithium ions can diffuse quickly and evenly in the positive electrode material during high-rate discharge, thereby improving the discharge efficiency and power density of the battery;
[0045] 2) Matching of electrolyte diffusion coefficient: Clarify the proportional relationship between the diffusion coefficient E of different electrolyte formulas and the diffusion coefficient M of the positive electrode active material, and achieve the best match between the electrolyte and the positive electrode by adjusting the electrolyte formula and lithium salt concentration to promote the rapid transmission of lithium ions in the electrolyte.
[0046] 3) Precise control of discharge rate: Define the maximum supported discharge rate RC, and calculate the value or value range of R based on the diffusion characteristics of the positive electrode active material layer and the electrolyte. By controlling the discharge rate, avoid battery overheating and shortened life due to excessive current.
[0047] 4) Innovative application of mathematical models: By defining A = (log (M) + R) 2 , B = log (E / M) + R, and using the ratio of A / B to quantify the discharge performance of the battery provides a theoretical basis for battery design and an effective tool for predicting and optimizing battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0049] Figure 1 This is a schematic diagram of the three-dimensional structure of a lithium-ion battery after assembly according to an optional embodiment of the present application;
[0050] Figure 2 It is a schematic diagram of the three-dimensional structure of the unfolded core portion of a lithium-ion battery according to an optional embodiment of the present application.
[0051] Figure 3 It is a schematic diagram of the planar structure of a positive electrode sheet of a lithium-ion battery in an optional embodiment of the present application;
[0052] Figure 4 It is a schematic diagram of the planar structure of a negative electrode sheet of a lithium-ion battery according to an optional embodiment of the present application;
[0053] Figure 5 is a schematic diagram of the migration path of lithium ions during the discharge process of a lithium ion battery of an optional embodiment of the present application;
[0054] Figure 6 The GITT relaxation curve is obtained by testing a button cell made of the positive electrode sheet and the separator of the lithium-ion battery in Example 1 of the present application;
[0055] Figure 7 This is an OCV variation curve obtained by conducting a test experiment on a button cell made of the electrolyte and diaphragm of the lithium-ion battery in Example 1 of the present application.
[0056] Figure numerals: 1 - shell, 2 - winding core, 21 - positive electrode sheet, 210 - positive electrode active material layer, 212 - positive electrode collector, 23 - separator, 25 - negative electrode sheet, 250 - negative electrode active material layer, 252 - negative electrode collector, 3 - electrolyte. DETAILED DESCRIPTION
[0057] Embodiments of the present embodiment are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present embodiment, and should not be construed as limiting the present embodiment.
[0058] In the description of this embodiment, it should be understood that descriptions involving orientation, such as up, down, front, back, left, right, etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing this embodiment and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on this embodiment.
[0059] In the description of this embodiment, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0060] In the description of this embodiment, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in this embodiment based on the specific content of the technical solution.
[0061] Please refer to Figure 1-Figure 4 , Figure 1 The figure shows a schematic diagram of the three-dimensional structure of a lithium-ion battery after being assembled according to an embodiment of the present application. Figure 2 A schematic diagram of the structure of a cylindrical battery core 2 is shown, Figure 3 Schematic diagram of the planar structure of the positive electrode sheet is shown. Figure 4 A schematic plan view of the structure of the negative electrode sheet 25 is shown.
[0062] The method for preparing the lithium-ion battery mentioned in the present application comprises the following steps:
[0063] S41: Preparation of positive electrode sheet 21: including positive electrode current collector 212 aluminum foil and positive electrode active material layer 210 coated on both sides of the aluminum foil; wherein, calculated by weight percentage, the positive electrode active material layer 210 includes 97% LiNi 0.8 Co 0.15 Al 0.05 O2, 0.4% carbon nanotube conductive agent, 1.6% conductive carbon black and 1% polyvinylidene fluoride PVDF binder, add the above substances into NMP and stir to form a positive electrode slurry with a solid content of 60%, and apply it on the positive electrode collector 212 to form a positive electrode sheet;
[0064] S42: Preparation of negative electrode sheet 25: including negative electrode current collector 252 copper foil and negative electrode active material layer 250 coated on both sides of the copper foil; wherein, calculated by weight percentage, the negative electrode active material layer 250 includes 96% silicon-carbon material (Si content 5%), 1.0% conductive agent acetylene black, 1% thickener CMC and 2% negative electrode binder polyacrylic acid, the above substances are added into deionized water and stirred to form negative electrode slurry with a solid content of 40%, which is coated on the negative electrode current collector 252 to form negative electrode sheet 25;
[0065] S43: Preparation of electrolyte 3: dissolving fully dried lithium salt LiPF6 in an organic solvent containing 1% ethylene carbonate to prepare electrolyte 3 with a lithium salt concentration of 1 mol / L;
[0066] S44: Production of diaphragm 23: A PE base film with a thickness of 9 μm, a ceramic coating with a thickness of 1 μm coated on both sides of the PE base film, and a PVDF coating with a thickness of 1 μm coated on both sides of the ceramic coating, and the air permeability of the diaphragm 23 is controlled to be 70s / 100mL≤≤180s / 100mL.
[0067] S45: Battery assembly: The positive electrode sheet 21 and the negative electrode sheet 25 are respectively rolled, slit and die-cut, and then wound together with the separator 23 to obtain a battery core 2. The core 2 is welded to the electrical connecting sheet and then loaded into the battery casing 1. After completing the injection, sealing and formation processes, a lithium-ion battery is obtained.
[0068] It can be understood that: the present application uses cylindrical lithium-ion batteries as battery samples in the embodiments, wherein the diameter of the battery is 10-50 mm, the height is 60-150 mm, and the ratio of height to diameter is greater than 1.6. The positive electrode active material can be one or more of lithium nickel cobalt manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate; the silicon-carbon material can be a mixture of at least two of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-carbon material, and silicon-oxygen material; please refer to Figure 1 and Figure 2The lithium-ion battery also includes a shell 1 for assembling and accommodating the core 2, and an electrical connection sheet for electrically connecting the positive and negative electrodes of the core 2 to the shell 1; the shell 1 can be a steel shell or an aluminum shell, and its open end is also connected to the cap through a rolling groove to complete the battery packaging. The positive and negative poles are also provided at the upper and lower ends of the battery core 2 designed for high energy density. The poles can be single, multiple or full poles, preferably full poles.
[0069] See also Figure 3 The positive electrode sheet 21 includes a positive electrode current collector 212 and a positive electrode active material layer 210 coated on at least one surface of the positive electrode current collector 212. The positive electrode current collector 212 includes a coated area and an uncoated area. At least a portion of the positive electrode uncoated area serves as a positive electrode ear. The positive electrode uncoated area occupies 1-10% of the area of the positive electrode current collector 212.
[0070] See also Figure 4 The negative electrode sheet 25 includes a negative electrode current collector 252 and a negative electrode active material layer 250 coated on at least one surface of the negative electrode current collector 252. The negative electrode current collector 252 includes a coated area and an uncoated area. At least a portion of the negative electrode uncoated area serves as a negative electrode ear. The negative electrode uncoated area occupies 2-11% of the area of the negative electrode current collector 252.
[0071] The first aspect of the present application provides a lithium ion battery, see Figure 5 , comprising a positive electrode sheet 21, a separator 23, a negative electrode sheet 25 and an electrolyte 3 for transmitting lithium ions, wherein the positive electrode sheet 21 comprises a positive electrode current collector 212 and a positive electrode active material layer 210 coated on at least one surface of the positive electrode current collector 212, and the lithium ion diffusion coefficient of the positive electrode active material is M cm 2 / s, the lithium ion diffusion coefficient of the electrolyte 3 is E cm 2 / s, the maximum discharge rate supported by the lithium-ion battery is RC, which satisfies:
[0072] A=(log(M)+R) 2 ;
[0073] B = log (E / M) + R;
[0074] 0≤A / B≤0.5.
[0075] Understandably, Figure 5 The spheres with moving directions in the figure refer to the migrating lithium ions. During the discharge process, the lithium ion groups will escape from the negative electrode active material 250 and pass through the electrolyte 3 and the separator 23 to be embedded in the positive electrode active material layer 210. Furthermore, they will continue to migrate from the surface layer to the inner layer of the positive electrode active material layer 210.
[0076] In some embodiments, the lithium-ion diffusion coefficient M of the positive electrode active material is a well-known parameter in the art. The lithium-ion diffusion coefficient M of the positive electrode active material can also be typically measured by conventional methods in the art. For example, it can be measured by the conventional GITT method in the art and calculated according to Fick's first and second laws. Specifically, the positive electrode sheet 21, the separator 23 that is not wound into the core 2, the electrolyte 3, the negative electrode sheet 25, and other accessories are assembled into a half-cell for GITT testing. The testing method can be carried out according to the "results and discussion" section in the literature "Yang etal., Electrochimica Acta, 2012, 66:88-93". The specific testing method is as follows:
[0077] S11: Prepare a button half-cell using the positive electrode sheet, the separator, and a lithium sheet (as the negative electrode of the battery) included in the lithium-ion battery. Charge and discharge the button cell at a rate of 0.1C at room temperature to calibrate the capacity, and take the discharge capacity at 0.1C as the calibrated capacity; then, at a rate of 0.1C, charge it to 50% of its calibrated capacity and let it stand for 15 min;
[0078] S12: Then, continuously charge the button cell at a constant current of 0.1C at room temperature for 5 min, record the initial charging voltage V1 and the final charging voltage V2, then stop charging and let it stand for 15 min, and record the initial standing voltage V3 and the final standing voltage V4; and
[0079] S13: The calculation formula for the lithium-ion diffusion coefficient M of the positive electrode active material is: M = (4 / πτ) * [(mV / nS)]^2 * [(ΔEs / ΔEt)]^2, where τ is the time of applying a constant current and τ << L^2 / M, m is the mass of the positive electrode active material included in the positive electrode sheet 21, V is the molar volume of the positive electrode active material in cm^3 / mol, n is the relative molecular mass of the positive electrode active material in g / mol, S is the contact area between the positive electrode sheet 21 and the electrolyte 3 in cm 2 , ΔEs = V4 - V1, ΔEt = V2 - V3, and L is the thickness of the positive electrode active material layer 210 included in the positive electrode sheet 21.
[0080] Furthermore, the testing method for the lithium-ion diffusion coefficient E of the electrolyte 3 can be carried out according to the "Experimental" section in the literature "Landesfeind J et al., Journal of The Electrochemical Society, 2019, 166(14): A3079 - A3097". The testing method for the lithium-ion diffusion coefficient E of the electrolyte 3 includes:
[0081] S21: taking the electrolyte 3 and the separator 23 used to manufacture the lithium-ion battery, measuring the tortuosity ε of the separator 23, and using the electrolyte 3, the separator 23, and two lithium sheets to manufacture a button battery, wherein the two lithium sheets serve as two electrodes of the button battery;
[0082] Specifically, the button battery assembly method is: take two lithium sheets, place polypropylene foil and the diaphragm 23 on top of one of the lithium sheets (the lithium sheet at the bottom), add the electrolyte 3, and then place another lithium sheet (the lithium sheet at the top) and a stainless steel gasket on the top of the diaphragm 23, and finally add a gasket to assemble a button battery, wherein the size of the lithium sheet at the bottom is: diameter 17mm, thickness 75μm; the size of the polypropylene foil is: inner diameter 17mm, outer diameter 19mm, thickness about 80μm; the diaphragm is a plasma-treated Nitto diaphragm, the size is: diameter 19mm, thickness 500μm; the amount of electrolyte added is 60μL, which is equivalent to 150% of the pore volume of the diaphragm; the size of the lithium sheet at the top is: diameter 17mm, thickness 450μm; the size of the stainless steel gasket is: diameter 16mm, thickness 1mm; it can be understood that the above-mentioned sheet structures are all stacked in a center-aligned manner, and the lithium sheet is a metal sheet made of lithium;
[0083] S22: The button cell is subjected to a 0.2 mA / cm 2 A constant alternating positive and negative current pulse is applied for 30 minutes, and then the current is turned off;
[0084] S23: measuring the change of the open circuit voltage (OCV) of the button battery over time to obtain an OCV relaxation curve; and
[0085] S24: The calculation formula of the lithium ion diffusion coefficient E of the electrolyte 3 is E=d^2*k*ε / (π^2), d is the thickness of the diaphragm 23, k is the natural logarithmic slope of the OCV relaxation curve, and ε is the tortuosity of the diaphragm 23.
[0086] It is understandable that the diaphragm tortuosity ε test method is
[0087] (1) disassembling a lithium-ion battery and obtaining its diaphragm 23;
[0088] (2) After soaking the diaphragm 23 in DMC (dimethyl carbonate) for two hours, the diaphragm 23 was rinsed with DMC three times, and the diaphragm 23 was baked in a vacuum oven at 60° C. for 4 hours until dry;
[0089] (3) Take two more pieces of copper foil and assemble them with the diaphragm 23 to form a symmetrical battery;
[0090] (4) The number of layers of the diaphragm 23 is set to 3, and the number of symmetrical batteries is not less than 3;
[0091] (5) performing an EIS test on the above symmetrical battery and obtaining the ionic resistance Rion of the separator 23;
[0092] (6) The tortuosity of the diaphragm 23 ε = (Rion*s*η*σ) / 3d', where Rion is the average value of the ionic impedance of the three-layer diaphragm test, s is the electrode area, η is the porosity of the diaphragm 23, σ is the conductivity of the electrolyte 3, and d' is the thickness of the single-layer diaphragm 23.
[0093] Furthermore, the test method of the maximum discharge rate RC includes:
[0094] S30: The test environment is room temperature: 25±2° C., and the lithium-ion battery during the test is not subjected to forced heating or cooling by air flow or liquid flow;
[0095] S31: at room temperature, charging the lithium-ion battery to a cut-off voltage at a rate of 0.1C, and standing for 30 minutes;
[0096] S32: at room temperature, discharge the lithium ion battery again at a rate of 0.1C to a cut-off voltage, let stand for 30 minutes, and record the discharge specific capacity; and
[0097] S33: Repeat S31 and S32, taking 0.5C rate as the basis, increasing the discharge rate by 0.5C each time until the discharge specific capacity at the discharge rate of RC is less than or equal to 80% of the discharge specific capacity at the discharge rate of 0.1C for the first time, RC being the maximum discharge rate supported by the lithium-ion battery.
[0098] The GITT test of the battery, full name: Galvanostatic Intermittent Titration Technique: constant current intermittent titration technique, induces composition changes on the surface of the active material in the working electrode by applying a series of constant current pulses, and then allows the battery to relax to a near equilibrium state under open circuit conditions. During the current pulse, the change in battery voltage is used to extract the square root time dependence of the diffusion process, and during the relaxation period, it is used to estimate the equilibrium thermodynamic property test, thereby providing detailed information about the diffusion rate of lithium ions in the positive electrode active material layer 210;
[0099] The OCV relaxation curve can reveal the dynamic behavior of the battery during the charge and discharge process, including the lithium ion insertion and deinsertion behavior during the charge process, as well as possible side reactions;
[0100] The discharge rate of a battery reflects the current intensity that the battery can withstand at different discharge rates, where the current intensity is also related to the rated capacity of the battery. The rate unit is usually expressed as "C", where "1C" means the current intensity at which the battery can be fully discharged or charged within 1 hour; specifically, if the rated capacity of a battery is 4.5Ah, then the current of 1C is 4.5A, that is, the battery can discharge or charge 4.5Ah of electricity within 1 hour. In addition, the charge and discharge cut-off voltages of batteries using different positive electrode active materials may be different. For example, the charge and discharge cut-off voltages of lithium-ion batteries using ternary nickel cobalt manganese oxide positive electrode active materials are 4.25V and 2.5V respectively, the charge and discharge cut-off voltages of lithium-ion batteries using spinel manganese oxide positive electrode active materials are 4.5V and 3.5V respectively, and the charge and discharge cut-off voltages of lithium-ion batteries using lithium iron phosphate positive electrode active materials are 3.65V and 2.0V respectively.
[0101] In some optional embodiments, the positive electrode sheet 21 satisfies at least one of the following conditions:
[0102] (a) The single-sided surface density of the positive electrode sheet is between 8 and 14 mg / cm 2 ;
[0103] (b) The compaction density of the positive electrode sheet is between 2.6 and 4.2 g / cm 3 ;
[0104] (c) The specific surface area of the positive electrode active material particles is between 0.1 and 25 m 2 / g;
[0105] (d) The particle size distribution of the positive electrode active material particles is 1-25 μm.
[0106] The above parameters are all important parameters that affect the lithium ion diffusion coefficient M of the positive electrode active material. When the A / B of the lithium ion battery is tested to be beyond the range of 0-0.5, the above parameters can be adjusted by adjusting the production process of the positive electrode sheet 21 to finally obtain a lithium ion battery that meets the standards.
[0107] The volume particle size distribution test of positive electrode active material particles can refer to national standards including GB / T19077-2016 "Particle Size Distribution Laser Diffraction Method" and GB / T 41949-2022 "Technical Requirements for Particle Laser Particle Size Analyzer".
[0108] The method for testing the compaction density of the positive electrode sheet 21 in the present application includes the following steps:
[0109] S1: Wash the sample positive electrode sheet 21 with dimethyl carbonate 2-4 times, and dry it in a 60°C oven for 4 hours to fully remove the dimethyl carbonate;
[0110] S2: Take a disc with an area of S' from the double-sided coating area of the sample positive electrode sheet 21, weigh it to get the sum of the mass of the positive electrode current collector 212 foil and the positive electrode active material layer 210 m1, and use a spiral micrometer to measure the sum of the thickness of the foil and the positive electrode active material layer 210 to be d1;
[0111] S3: scrape off all the powder on the surface of the disc, wipe the surface of the disc with NMP to fully remove the powder, and fully dry the disc, weigh the disc again to obtain the mass of the foil m2, and use the spiral micrometer again to measure the thickness of the foil d2; and
[0112] S4: Calculate the compacted density as (m1-m2) / [S'*(d1-d2)] (unit: g / cm3).
[0113] The method for testing the single-side surface density of the positive electrode sheet 21 in the present application includes the following steps:
[0114] S1: Wash the sample positive electrode sheet 21 with dimethyl carbonate for 2-5 times, and dry it in a 60°C oven for 4 hours to fully remove the dimethyl carbonate;
[0115] S2: Take a disc with a cross-sectional area of S' from the double-sided coating area of the sample positive electrode sheet 21, and weigh it to obtain the sum of the masses m1 of the positive electrode current collector 212 foil and the positive electrode active material layer 210;
[0116] S3: Scrape off all the powder on the surface of the disc, wipe the surface of the disc with NMP to fully remove the powder, and fully dry the disc, and weigh the disc again to obtain the foil mass m2;
[0117] S4: Calculate the single-surface surface density as (m1-m2) / (2S') (unit: g / cm2).
[0118] The test method for the specific surface area of positive electrode active material particles can refer to the national standard "GBT19587-2017 Determination of the specific surface area of solid substances by gas adsorption BET method".
[0119] A mathematical relationship model is established between the lithium ion diffusion coefficient M of the positive electrode active material, the lithium ion diffusion coefficient E of the electrolyte 3, and the maximum discharge rate RC supported by the lithium ion battery. Based on this mathematical model, combined with the corresponding experimental measurement data:
[0120] First, by precisely controlling the diffusion coefficient M of the positive electrode active material, it is possible to ensure that lithium ions can diffuse quickly and evenly in the positive electrode active material layer 210 during high rate discharge, thereby improving the discharge efficiency and power density of the battery;
[0121] Secondly, the proportional relationship between the diffusion coefficient E of the electrolyte 3 and the diffusion coefficient M of the positive electrode active material is clarified, and the best match with the positive electrode active material layer 210 is achieved by adjusting the formula of the electrolyte 3 and the lithium salt concentration, so as to promote the rapid transmission of lithium ions in the electrolyte 3;
[0122] Third, accurately control the discharge rate: define the maximum supported discharge rate RC, calculate the value or value range of R based on the diffusion characteristics of the positive electrode active material layer 210 and the electrolyte 3, and control the discharge rate to avoid battery overheating and shortened life due to excessive current;
[0123] Fourthly, innovative applications include mathematical models in three dimensions: E, M, and R: By defining A = (log (M) + R) 2 , B = log (E / M) + R, and using the ratio of A / B to quantify the discharge performance of the battery provides a theoretical basis for battery design and an effective tool for predicting and optimizing battery performance.
[0124] Specifically, before the battery is completed, by determining the value or range of any one of M, E, and R of the battery raw material or the semi-finished battery, the range of the other two data is solved, and the battery system is improved and adjusted in a targeted manner, it is easy to prepare a lithium-ion battery in which M and E are adapted, the diffusion rate of lithium ions in the electrolyte 3 and the positive electrode active material layer 210 is sufficient to support continuous and stable output at the RC rate and maintain a long cycle life; and for finished batteries that have been assembled, the mathematical model can also be used to evaluate the battery performance and solve the maximum output rate RC actually supported by the lithium-ion battery, so as to avoid battery overheating and shortened life due to excessive discharge current, and provide guidance for the long-term use of the battery.
[0125] In some optional embodiments, the positive electrode active material layer 210 includes the following components:
[0126] A positive electrode active material, as the positive electrode active material, the weight percentage is 80% to 97%;
[0127] Conductive agent, 2% to 10% by weight; and
[0128] The binder has a weight percentage of 1% to 10%.
[0129] Furthermore, the crystal phase of the positive electrode active material is one of a layered structure crystal phase, a spinel structure crystal phase and an olivine structure crystal phase.
[0130] Among them, the layered positive electrode material allows lithium ions to be intercalated and deintercalated between layers, providing a higher specific capacity and good electrochemical performance, and therefore has a high theoretical capacity to enhance the energy storage performance per unit volume of the battery. The spinel and / or olivine crystal phase positive electrode material, on the one hand, effectively enhances the overall stability of the positive electrode active material layer 210; on the other hand, it can also form a three-dimensional channel for lithium ions to diffuse uniformly in the positive electrode active material layer 210, increase the lithium ion diffusion coefficient M of the positive electrode active material layer 210, and provide the necessary conditions for the high rate output of the battery.
[0131] In some optional embodiments, the positive electrode active material of the layered structure crystal phase is lithium nickel cobalt metal oxide, chemical formula LiNi x Co y D z O2, where 0.6≤x≤0.9, 0.1≤y≤0.4, z=1-x–y, and D is Mn or Al;
[0132] The positive electrode active material of the spinel structure crystal phase is lithium manganese oxide LiMn2O4;
[0133] The positive electrode active material of the olivine structure crystal phase is lithium iron phosphate LiFePO4 or lithium iron manganese phosphate LiMn x Fe 1- x PO4.
[0134] In some optional embodiments, the positive electrode active material further comprises a doping element, and the doping element is at least one of Al, Zr, Sr, Sb, Mg, Ti, W, Nb, Y, Ca, Ba, B, and F. Any of the doping elements improves the cycle performance and stability of the positive electrode active material layer 210 by lattice doping and substitution, surface modification and coating, improving electronic and ionic conductivity, reducing cation mixing and / or inhibiting lattice oxygen loss. To further specify, the doping of elements such as Ti, Zr, and Nb can improve the lattice stability of the positive electrode active material layer 210 such as high nickel ternary, reduce the cation mixing phenomenon of transition metal ions such as Ni, Mn, and Co, and reduce the lattice structure changes during the charge and discharge process, thereby improving the cycle stability of the positive electrode active material layer 210; Al doping can promote the formation of BCC phase, thereby improving the corrosion resistance of the material; Al and Nb can improve the electronic conductivity of the positive electrode active material layer 210; Ti and Zr doping can also improve the diffusion kinetics of lithium ions to improve the rate performance and cycle stability of the battery; for the lithium-rich manganese-based positive electrode active material layer 210, the redox reaction of oxygen elements is the source of its high capacity, but it is also accompanied by the risk of lattice oxygen loss. The introduction of elements such as Ti and Zr can increase the hybridization degree of transition metal atoms and oxygen atoms TM-O and reduce the precipitation of oxygen. At the same time, doping with the above elements can also improve the mechanical stability and thermal stability of the positive electrode active material layer 210, and reduce the risk of structural damage and thermal runaway caused by volume expansion and contraction during the charge and discharge process.
[0135] In some optional embodiments, the surface of the positive electrode active material is also modified by coating and / or atomic doping, wherein the coating modification includes coating a layer of metal oxide nanolayer on the surface of the positive electrode active material, and the atomic doping modification includes doping metal atoms with an electronegativity less than 2 on the surface of the positive electrode active material. The protective film is formed by the metal oxide nanocoating, which reduces the direct contact between the positive electrode active material and the electrolyte 3, thereby inhibiting the occurrence of side reactions, reducing the deactivation of the positive electrode active material, and improving the cycle performance of the battery; the atomic doping modification can change the electronic structure and lattice parameters of the positive electrode active material, preferably, metal elements with an electronegativity less than 2 such as sodium, magnesium, and zinc, which can improve the structural stability and electrochemical performance of the material. In the specific implementation process, the coating modification can also use aluminum oxide Al2O3, titanium oxide TiO2, Nb2O5, SrO, ZrO2, etc. These metal oxides have ceramic-like properties, which are convenient for forming a relatively stable and dense protective layer. In addition, it can be added in the form of solid powder, which is convenient for mixing with other materials in the positive electrode active material layer 210 to form a positive electrode slurry, and is evenly coated on the surface of the positive electrode current collector 212 .
[0136] In some optional embodiments, the electrolyte 3 comprises the following components:
[0137] A lithium salt, including lithium hexafluorophosphate, wherein the total molar concentration of the lithium salt is 0.5M-2.0M;
[0138] The organic solvent mixture comprises one or more of ethylene carbonate, dimethyl carbonate, fluoroethylene carbonate and vinyl sulfate.
[0139] In some optional embodiments, a modifying additive is also added to the electrolyte 3, and the weight ratio of the additive to the electrolyte 3 system is 0.5%-2%, and the modifying additive includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(oxalate borate) and triethyl phosphate. Lithium bis(fluorosulfonyl)imide can improve the conductivity of the electrolyte 3, thereby improving the lithium ion diffusion coefficient E of the electrolyte 3; lithium bis(oxalate borate) does not contain fluorine, which reduces the generation of byproduct fluoride and reduces the risk of thermal runaway of the battery under high temperature conditions; triethyl phosphate can be used as a flame retardant to improve the thermal stability of the electrolyte 3 system and ensure the safety of the battery. It is understandable that the means of improving conductivity and improving system stability may conflict with each other. In the specific implementation process, the amount of additives added with two functions is coordinated and balanced to achieve the simultaneous improvement of conductivity and system stability.
[0140] The second aspect of the present application provides an electric device, comprising the lithium ion battery according to the above. Since the lithium ion battery has the above-mentioned beneficial effects, the electric device provided by the present application has the characteristics of continuous stable high rate output and high cycle retention rate.
[0141] The technical solution of the present application is explained below in conjunction with Examples 1-31. The battery specifications in the following examples are: 21700 cylindrical lithium-ion batteries with full tabs, and the positive electrode active material exists in the form of positive electrode material particles at the level of studying battery electrochemical kinetics.
[0142] The relevant parameter settings involved in the present embodiments 1-4 are as follows: Table 1 and Table 2:
[0143] Table 1
[0144]
[0145] Table 2
[0146]
[0147] The relevant parameter settings involved in the present embodiments 5-8 are as follows: Table 3 and Table 4:
[0148] Table 3:
[0149]
[0150]
[0151] Table 4
[0152]
[0153] The relevant parameter settings involved in the present embodiments 9-12 are as follows: Table 5 and Table 6:
[0154] Table 5
[0155]
[0156]
[0157] Table 6
[0158]
[0159] The relevant parameter settings involved in this embodiment 13-14 are as follows in Table 7:
[0160] Table 7
[0161]
[0162] Table 8
[0163]
[0164]
[0165] Table 9
[0166]
[0167] The relevant parameter settings involved in the present embodiment 19-20 are as follows in Table 10:
[0168] Table 10
[0169]
[0170]
[0171] The relevant parameter settings involved in the present embodiments 21-24 are as follows: Table 11 and Table 12:
[0172] Table 11
[0174]
[0175] Table 12
[0176]
[0177]
[0178] The relevant parameter settings involved in the present embodiments 25-27 are as follows: Table 13 and Table 14:
[0179] Table 13
[0180]
[0181] Table 14
[0182]
[0183] The relevant parameter settings involved in Comparative Examples 1-4 are as follows: Table 15 and Table 16:
[0184] Table 15
[0185]
[0186] Table 16
[0187]
[0188] The diffusion coefficient M of the positive electrode active material, the diffusion coefficient E of the electrolyte 3, and the maximum supported discharge rate RC were measured for the above-mentioned Examples 1-27 and Comparative Examples 1-4 respectively according to the above-mentioned test method. Figure 6 and Figure 7 , are the relaxation curve and OCV change curve of Example 1;
[0189] According to the formula A=(log(M)+R) 2 And B=(log(E / M)+R), calculate the value of A / B, the calculation results are shown in Table 17.
[0190] Table 17
[0191]
[0192]
[0193] The lithium-ion batteries in the above embodiments are prepared using the diffusion coefficient M of the positive electrode active material and the diffusion coefficient E of the electrolyte 3 defined by the mathematical model provided in the present application, and the maximum discharge rate RC supported by the above lithium-ion batteries is measured. It can be seen from the test results in Table 19 that within the limited range, the lithium-ion batteries of Examples 1-27 all meet the formula 0≤A / B≤0.5, and the predicted maximum discharge rate RC can be used to guide the application direction of the battery. By controlling the maximum discharge rate RC, the battery overheating and shortened life caused by excessive current can be avoided. The lithium-ion batteries of Comparative Examples 1-4 all exceed the constraint range of the formula 0≤A / B≤0.5, and correspondingly, the maximum discharge rate RC is not ideal and it is difficult to meet the demand for high-rate output.
[0194] In summary, the mathematical model described in the present application can be used in lithium-ion batteries to measure the diffusion coefficient M of the positive electrode active material layer 210 and the diffusion coefficient E of the electrolyte 3, and calculate the maximum supported discharge rate range through a formula, so as to optimize the discharge rate, effectively improve efficiency and save costs, and at the same time, charge and discharge tests on the battery within a suitable discharge rate range can improve the cycle life of the battery.
[0195] In the description of this specification, reference to the terms "some embodiments", "an example", or similar descriptions means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment are included in at least one embodiment or example. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0196] Although examples of the present embodiment have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present embodiment, and the scope of the present embodiment is defined by the claims and their equivalents.
Claims
1. A lithium-ion battery, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte for transmitting lithium ions, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer containing a positive electrode active material coated on at least one surface of the positive electrode current collector, characterized in that: The lithium ion diffusion coefficient of the positive electrode active material at room temperature is M cm 2 / s, the lithium ion diffusion coefficient of the electrolyte at room temperature is E cm 2 / s, the maximum discharge rate supported by the lithium-ion battery is RC, which satisfies: A=(log(M)+R) 2 ; B = log (E / M) + R; 0≤A / B≤0.
5.
2. The lithium-ion battery according to claim 1, characterized in that The positive electrode active material layer comprises the following components: The positive electrode active material has a weight percentage of 80% to 97%; Conductive agent, 2% to 10% by weight; and The binder has a weight percentage of 1% to 10%.
3. The lithium-ion battery according to claim 2, characterized in that: The crystal phase of the positive electrode active material is one of a layered structure crystal phase, a spinel structure crystal phase and an olivine structure crystal phase.
4. The lithium-ion battery according to claim 3, characterized in that: The positive electrode active material of the layered structure crystal phase is lithium nickel cobalt metal oxide, the chemical formula of which is LiNi x Co y D z O2, where 0.5≤x≤0.9, 0.1≤y≤0.4, z=1-x–y, and D is Mn or Al; The positive electrode active material of the spinel structure crystal phase is lithium manganese oxide LiMn2O4; The positive electrode active material of the olivine structure crystal phase is lithium iron phosphate LiFePO4 or lithium iron manganese phosphate LiMn x Fe 1-x PO4, 0.1≤x≤0.
8.
5. The lithium-ion battery according to claim 2, characterized in that: The positive electrode active material also contains a doping element, and the doping element is at least one of Al, Zr, Sr, Sb, Mg, Ti, W, Nb, Y, Ca, Ba, B, and F.
6. The lithium-ion battery according to claim 2, characterized in that: The surface of the positive electrode active material is also modified by coating and / or atomic doping. The coating modification includes coating a layer of metal oxide nanolayer on the surface of the positive electrode active material. The atomic doping modification includes doping metal atoms with an electronegativity less than 2 on the surface of the positive electrode active material.
7. The lithium-ion battery according to claim 1, characterized in that: The electrolyte comprises the following components: A lithium salt, including lithium hexafluorophosphate, wherein the total molar concentration of the lithium salt is 0.5M-2.0M; The organic solvent mixture comprises one or more of ethylene carbonate, dimethyl carbonate, fluoroethylene carbonate and vinyl sulfate.
8. The lithium-ion battery according to claim 7, characterized in that: The electrolyte is also added with a modification additive, which includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate) and triethyl phosphate, and the weight proportion of the modification additive in the electrolyte system is 0.5%-2%.
9. The lithium-ion battery according to claim 1, wherein the positive electrode sheet satisfies at least one of the following conditions: (a) The single-sided surface density of the positive electrode sheet is 8-14 mg / cm 2 ; (b) The compaction density of the positive electrode sheet is 2.6-4.2 g / cm 3 ; (c) The specific surface area of the positive electrode active material particles is 0.1-25 m 2 / g; (d) The particle sizes D10-D90 of the positive electrode active material particles are distributed in the range of 1-25 μm.
10. The lithium ion battery according to claim 1, characterized in that: The testing method of the lithium ion diffusion coefficient M of the positive electrode active material includes: S11: The positive electrode sheet, the separator and the lithium sheet contained in the lithium-ion battery are made into a button-type half-cell, and the charge and discharge are carried out at room temperature at a rate of 0.1C to calibrate the capacity, and then the constant current is charged at a rate of 0.1C to 50% of the calibrated capacity, and the battery is left for 15 minutes; S12: charging the button battery at room temperature at a constant current of 0.1C for 5 minutes, recording the charging start voltage V1 and the charging end voltage V2, then stopping the charging, leaving it for 15 minutes, and recording the leaving start voltage V3 and the ending voltage V4; and S13: The calculation formula for the lithium ion diffusion coefficient M of the positive electrode active material is: M = (4 / πτ) * [(mV / nS)]^2 * [(ΔEs / ΔEt)]^2, where τ is the time for applying a constant current and τ << L^2 / M, m is the mass of the positive electrode active material contained in the positive electrode sheet, V is the molar volume of the positive electrode active material in cm^3 / mol, n is the relative molecular mass of the positive electrode active material in g / mol, S is the contact area between the positive electrode sheet and the electrolyte in cm 2 , ΔEs = V4 - V1, ΔEt = V3 - V2, and L is the thickness of the positive electrode active material layer contained in the positive electrode sheet.
11. The lithium ion battery according to claim 1, characterized in that: The specific test method of the lithium ion diffusion coefficient E of the electrolyte is: S21: taking the electrolyte and the separator contained in the lithium-ion battery, measuring the tortuosity ε of the separator, and using the electrolyte, the separator and two lithium sheets to make a button battery, wherein the two lithium sheets serve as two electrodes of the button battery; S22: Apply 0.2 mA / cm to the button cell at room temperature 2 A constant alternating positive and negative current pulse is applied for 30 minutes, and then the current is turned off; S23: measuring the change of the open circuit voltage (OCV) of the button battery over time to obtain an OCV relaxation curve; and S24: The calculation formula of the lithium ion diffusion coefficient E of the electrolyte is E=d^2*k*ε / (π^2), d is the thickness of the diaphragm, k is the natural logarithmic slope of the OCV relaxation curve, and ε is the tortuosity of the diaphragm.
12. The lithium ion battery according to claim 1, characterized in that: The test method of the maximum discharge rate RC includes: S31: at room temperature, charging the lithium-ion battery to a charge cut-off voltage using a rate of 0.1C, and standing for 30 minutes; S32: at room temperature, the lithium ion battery is discharged to a discharge cut-off voltage at a rate of 0.1C, left to stand for 30 minutes, and the discharge specific capacity is recorded; and S33: Repeat S31 and S32, taking 0.5C rate as the basis, increasing the discharge rate by 0.5C each time until the discharge specific capacity at the discharge rate of RC is less than or equal to 80% of the discharge specific capacity at the discharge rate of 0.1C for the first time, RC being the maximum discharge rate supported by the lithium-ion battery.
13. An electrical device, characterized in that: Comprising a lithium ion battery according to any one of claims 1-12.